Seeing teacher-designer-curriculum research through an ergonomic lens: Commentary. (2019) - Drake, Corey; Remillard, Janine T.
Highlights: Reviews and synthesizes articles in this volume. Discusses focus, methods, timescale, and use of technology in ergonomic research. Provides potential directions for future work in curriculum ergonomics. Abstract: In this commentary, we look across the articles in this volume to address the question – what does an ergonomic lens help us see that existing analytic lenses do not? Given that research using an ergonomic lens is relatively new and still emerging, we address this question from the perspectives of both what the current research, as represented in this volume, can help us see and understand, as well as what future research might consider and help us understand more deeply.